2013
DOI: 10.1103/physrevb.88.195303
|View full text |Cite
|
Sign up to set email alerts
|

Resonance fluorescence spectrum of ap-doped quantum dot coupled to a metallic nanoparticle

Abstract: The resonance fluorescence spectrum (RFS) of a hybrid system consisting of a p-doped semiconductor quantum dot (QD) coupled to a metallic nanoparticle (MNP) is analyzed. The quantum dot is described as a four-level atom-like system using the density matrix formalism. The lower levels are Zeeman-split hole spin states and the upper levels correspond to positively charged excitons containing a spin-up, spin-down hole pair and a spin electron. A linearly polarized laser field drives two of the optical transitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…This work is related to previous works carried out by us [17] and other authors [14-16, 18, 19] on the spectral properties of the spontaneous photons produced in externally driven quantum systems coupled to a metallic nanostructure. These studies revealed the possibility of changing the linewidth and location of the different sidebands of the spectra of the spontaneous photons arising from the back-action of the electric field generated by the metallic nanostructure on the quantum system (exciton-plasmon coupling).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…This work is related to previous works carried out by us [17] and other authors [14-16, 18, 19] on the spectral properties of the spontaneous photons produced in externally driven quantum systems coupled to a metallic nanostructure. These studies revealed the possibility of changing the linewidth and location of the different sidebands of the spectra of the spontaneous photons arising from the back-action of the electric field generated by the metallic nanostructure on the quantum system (exciton-plasmon coupling).…”
Section: Introductionmentioning
confidence: 62%
“…The ultracompact optical mode volume achieved in plasmon nanostructures leads to a large resonant enhancement of the local field near the MNP [1][2][3][4], as well as the modification of spontaneous emission rates of the emitter's optical transitions [5][6][7][8][9][10][11]. The exciton-plasmon coupling has received a great deal of attention leading to interesting phenomena like changes in photoluminescence lifetimes [12], in photon statistics [13], in the resonance fluorescence [14][15][16][17][18][19], in plasmon-induced quantum interference effects [20][21][22], in the control over population dynamics [23][24][25][26], and over nonlinear optical processes [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…(14). The above mentioned mechanisms strongly depend on the QD-nanoantenna distance R. These mechanisms have been explored in the context of obtaining hole spin initialization [13] and in the case of considering the modification in the resonance fluorescence spectrum arising from the plasmonic interaction [38].…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The calculation of S inc (ω) requires the calculation of the two-time correlation function, which can be performed by means of the quantum-regression theorem [55,54] (see Ref. [38] for details). The central line exhibits a three peak structure.…”
Section: Plasmonic Effects On the Photon Statistics Of The Fluorescenmentioning
confidence: 99%
See 1 more Smart Citation